AN ANALYSIS OF SLANGS IN “DON’T LOOK UP” MOVIE - Natasya Octavionica; Dahnilsyah Dahnilsyah; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The aims of this research are to identify the types and functions of slang in the film “Don’t Look Up” based on Allan and Burridge theory. This research was conducted by doing a descriptive qualitative method with a content analysis design. The source of this research is taken from the movie and the script of “Don’t Look Up” movie directed by Adam McKay. Based on the research result, there are thirty-four slangs in the movie “Don’t Look Up”. There are five types of slang in the theory of Allan and Burridge, however, only four types were found in the movie. Those are fresh and creative, imitative, flippant, and acronyms. For the functions of slang, there were seven functions of slang based on Allan and Burridge theory. However, only six functions of slang that were found in the movie are as follows to address, to humiliate, to initiate a relaxed conversation, to communicate impression, to reveal anger, and to show intimacy.Key Words: sociolinguistics, slang, movie